ROLE OF TRANEXAMIC ACID IN CONTROLLING BLOOD LOSS IN TOTAL HIP ARTHROPLASTY - CHAUHAN, MANISH S.; MAHMOOD, SYED T.; CHATERJII, GAUTAM; SHAKYA, MANMOHAN; PAL, VISHNU; SIDDHARTHA, P. V. (International Journal of Current Pharmaceutical Research, 2024)
Objective: The incidence of total hip arthroplasty (THA) is on the rise, often resulting in significant blood loss. It has been observed that Tranexamic acid (TXA) can diminish the blood loss experienced during the perioperative period of hip joint arthroplasty. Nonetheless, the optimal method of administering TXA remains a topic of debate. So, we studied the role of Tranexamic Acid in Controlling Blood Loss in Total Hip Arthroplasty. Methods: In Prospective group data: By giving a dose of 15 mg/kg of Tranexamic acid, intravenously 15 min before given incision and 15 mg/kg topically after the closure of the hip joint capsule. Retrospective data from the records of previous patients who were administered intravenous tranexamic acid while undergoing THR in the past 3 years with 30 cases in each group. Information was gathered regarding the volume of blood loss, levels of hemoglobin, frequency of transfusions, and the incidence of deep vein thrombosis and pulmonary embolism. Results: The mean operation times were approximately 43.5±9.0 min and 42.2±8.0 min in group A and group B, respectively. The operation time and intra-operative blood loss show insignificant differences in prospective and retrospective groups. The post-operative blood loss, total blood loss, and decrease in haemoglobin level depicted insignificant differences in prospective and retrospective groups. There were insignificant differences in terms of blood loss and systemic complications between tranexamic acid administration methods. Conclusion: Tranexamic acid is effective in minimizing blood loss following surgery as well as the overall blood loss associated with total hip arthroplasty, according to the data reviewed and the results of this study showing non-inferior efficacy of topical TXA and IV TXA with IV TXA, we proposed that topical administration of 15 mg/ml of TXA before wound closure was a simple, safe, feasible and effective prophylactic measure with minimal adverse effects. The use of this method proved to be economical, effectively decreasing bleeding, diminishing the necessity for additional blood transfusions, and averting the possibility of surgical intervention due to excessive bleeding.